Early education and care, and reconceptualizing play - Reifel, Robert Stuart; Brown, Mac H. (Advances in early education and day care, 2001)
This volume addresses two major areas of inquiry in the field of early childhood education and care. The first section of the book includes scholarly reviews on early childhood education and care and its conceptual bases. Programme curriculum and implementation are explored, including theoretically driven programmes and programme evaluations. Traditional perspectives on early childhood outcomes are detailed, alongside comparative analyses of early childhood practice from an international perspective. Section two presents the first in a series on reconceptualizing play. Traditional views of play, as an abiding element of early childhood practice, are critiqued. Questions about conceptions of play are raised by historical, ethical, cross-cultural, narrative, and theoretical treatments of play practices. These views are designed to stimulate thought about our most basic ideas of play and children.